HUBUNGAN ANTARA JENIS KELAMIN DAN OPTIMISME DENGAN COLLEGE STUDENT SUBJECTIVE WELL-BEING - Septa Lia Ariska; Asri Mutiara Putri; Junaidi Junaidi (JURNAL PSIKOLOGI MALAHAYATI, 2021)
ABSTRACT: THE RELATIONSHIP BETWEEN GENDER, OPTIMISME, AND COLLEGE STUDENT SUBJECTIVE WELL-BEING One indicators of college student mental health is college student subjective well-being or abbreviated CSSWB. CSSWB in college students can be influenced by several factor, including gender and optimism . This research aims to determine the relationship between gender and optimism towards college student subjective well-being. This research is a quantitative research conducted on 423 college student from semesters 4 until 8 in Bandar Lampung. Data collection in this research using college student subjective well-being scale, optimism scale likert model, and demographic data. Thdta analyzed using using multiple regression. The result show that optimism is the main predictor in exlaining CSSWB. Further research, is expected to study other variables which can also affect college student subjective well-being. Keyword : Gender, Optimism, College Student Subjective Well-being, College Student Salah satu indikator kesehatan mental mahasiswa adalah college student subjecvtive well-being atau disingkat CSSWB. CSSWB pada mahasiswa dapat dipengaruhi oleh beberapa faktor antara lain jenis kelamin dan optimisme. Penelitian ini bertujuan untuk mengetahui hubungan antara jenis kelamin dan optimisme dengan college student subjective well-being. Penelitian ini merupakan penelitian kuantitatif yang dilakukan pada 423 mahasiswa semester 4 sampai 8 di Bandar Lampung. Teknik pengumpulan data dalam penelitian ini menggunakan skala College Student Subjective Well-being Questionary, skala Optimisme model likert, serta data demografi. Data dianalisis menggunakan regresi berganda. Hasil penelitian menunjukkan optimisme sebagai prediktor utama dalam menjelaskan college student subjective well-being. Penelitian selanjutnya diharapkan dapat menambahkan variabel lain dalam melihat faktor-faktor yang mempengaruhi college student subjective well-being. Kata Kunci : Jenis Kelamin, Optimisme, College Student Subjective Well-being, Mahasiswa